Kininogen and Ferritin in Tumorigenesis - Song, Yufeng (Wake Forest University, 2010)
High molecular weight kininogen (HK) is a plasma glycoprotein which serves as a cofactor in the intrinsic coagulation cascade, and it is also known as an inhibitor of cysteine proteases. HKa can interact with a variety of cells including endothelial cells, neutrophils, monocytes and platelets. When bound to endothelial cells, HK can be cleaved by plasma kallikrein to release bradykinin and the two chain high molecular weight kininogen, HKa. HKa has been shown to inhibit angiogenesis both in vitro and in vivo. Ferritin is a 24-subunit iron-storage protein which is mostly located intracellularly. Small amounts of ferritin also exist in serum and are often elevated during inflammation and some malignancies. Previous studies have demonstrated that ferritin binds to HKa and antagonizes its antiangiogenic effects, enhancing the proliferation, migration and survival of HKa-treated endothelial cells. Thus far, several binding sites for HKa on the endothelial cell surface have been identified including urokinase plasminogen activator receptor (uPAR, CD87), cytokeratin 1(CK1), globular “head” of C1q (gC1q-R) and tropomyosin, of which uPAR is the most studied and most relevant to tumorigenesis. Tumor cells frequently overexpress uPAR. The work presented here focuses on the effects of HKa and ferritin on cancer cells and the signaling pathways initiated by HKa and ferritin in endothelial cells. HKa was shown to inhibit the proliferation, migration, adhesion and clonogenic growth of cancer cells. Ferritin did not block HKa’s effects on these cells. To assess if uPAR plays a role in determining sensitivity to HKa, uPAR levels were detected in cancer cells using by western blot. Most of the cancer cells tested expressed uPAR. However, correlation analysis showed no linear correlation between the sensitivity of cells to HKa in terms of its effect on cell proliferation and uPAR level. We also assessed HKa’s effect on signaling pathways in endothelial cells. Both HKa and ferritin inhibited uPA-induced phosphorylation and activation of ERK1/2. HKa did not inhibit phosphorylation of FAK and paxillin. Neither HKa nor ferritin affected the phosphorylation and activation of Akt. Flow cytometry analysis showed that both HKa and ferritin bound to endothelial cells and that ferritin only slightly decreased HKa’s binding to endothelial cells. Overall, these findings defined the novel roles for HKa and ferritin in cancer cells and preliminarily explored the signaling pathways initiated by HKa and ferritin in endothelial cells.
Keywords: Kininogen; Ferritin; Tumorigenesis